Effectiveness of intra-articular lidocaine injection for reduction of anterior shoulder dislocation: randomized clinical trial - Tamaoki, Marcel Jun Sugawara; Faloppa, Flavio; Wajnsztejn, André; Netto, Nicola Archetti; Matsumoto, Marcelo Hide; Belloti, João Carlos (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Shoulder dislocation is the most common dislocation among the large joints. The aim here was to compare the effectiveness of reduction of acute anterior shoulder dislocation with or without articular anesthesia. DESIGN AND SETTING: Prospective randomized trial conducted in Escola Paulista de Medicina, Universidade Federal de São Paulo (EPM-Unifesp). METHODS: From March 2008 to December 2009, 42 patients with shoulder dislocation were recruited. Reductions using traction-countertraction for acute anterior shoulder dislocation with and without lidocaine articular anesthesia were compared. As the primary outcome, pain was assessed through application of a visual analogue scale before reduction, and one and five minutes after the reduction maneuver was performed. Complications were also assessed. RESULTS: Forty-two patients were included: 20 in the group without analgesia (control group) and 22 in the group that received intra-articular lidocaine injection. The group that received intra-articular lidocaine had a statistically greater decrease in pain over time than shown by the control group, both in the first minute (respectively: mean 2.1 (0 to 5.0), standard deviation, SD 1.3, versus mean 4.9 (2.0 to 7.0, SD 1.5; P < 0.001) and the fifth minute (respectively: mean 1.0; 0 to 3.0; SD = 1.0 versus mean 4.0; 1.0 to 6.0; SD = 1.4; P < 0.001). There was one failure in the control group. There were no other complications in either group. CONCLUSION: Reduction of anterior shoulder dislocation using intra-articular lidocaine injection is effective, since it is safe and diminishes the pain. CLINICAL TRIAL REGISTRATION: ISRCTN27127703.